2013
DOI: 10.1146/annurev-med-061511-134747
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metabolomics to Diagnosis of Insulin Resistance

Abstract: Metabolomics, the global interrogation of the biochemical components in a biological sample, has become an important complement to genomics and proteomics to aid in the understanding of pathophysiology. Major advantages of metabolomics are the size of the metabolome relative to the genome or proteome and the fact that it provides a view of the existing biochemical phenotype. As such, metabolomics is fast becoming an important discovery tool for new diagnostic and prognostic biomarkers. Although many methods ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 38 publications
0
43
0
4
Order By: Relevance
“…Metabolites represent an intermediate biological process that bridges gene function, nongenetic factors, and phenotypic end points (13,14). Numerous studies have shown that metabolic phenotypes can provide novel insights into gene function, mechanisms of disease pathogenesis, and biomarkers for disease diagnosis and prognosis (13,(15)(16)(17)(18)(19)(20)(21). MS, in combination with liquid chromatography (LC) and GC, has become the main platform for metabolomic analysis.…”
Section: Liningmentioning
confidence: 99%
“…Metabolites represent an intermediate biological process that bridges gene function, nongenetic factors, and phenotypic end points (13,14). Numerous studies have shown that metabolic phenotypes can provide novel insights into gene function, mechanisms of disease pathogenesis, and biomarkers for disease diagnosis and prognosis (13,(15)(16)(17)(18)(19)(20)(21). MS, in combination with liquid chromatography (LC) and GC, has become the main platform for metabolomic analysis.…”
Section: Liningmentioning
confidence: 99%
“…Metabolomic studies in metabolic diseases 31 have been used to identify novel biomarkers that associate with IR 23,32,33 and predict T2DM. [34][35][36] The three metabolites used in the test have a number of potential roles in metabolic pathways relevant to insulin action, insulin secretion, or β-cell function.…”
Section: Metabolite Biomarkers Of Insulin Resistancementioning
confidence: 99%
“…Most reported elevated plasma levels of branched-chain amino acids (BCAA; leucine, isoleucine, valine) in obese children, adolescents, and adults compared with their lean counterparts (1,5,18,29,32,33,50,58), and weight loss was associated with lower BCAA levels (39). Circulating alanine, phenylalanine, tyrosine, glutamate/ glutamine, aspartate/asparagine, and arginine have also been shown to be increased in obese individuals (33).…”
mentioning
confidence: 99%